2015
DOI: 10.18632/oncotarget.3950
|View full text |Cite
|
Sign up to set email alerts
|

Tie-2 regulates the stemness and metastatic properties of prostate cancer cells

Abstract: AbstrAct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
(41 reference statements)
3
18
0
Order By: Relevance
“…Osteoblast differentiation was assessed by measuring osteoblast differentiation markers by real‐time PCR, as described previously . The cell adhesion assay was undertaken as described previously . Briefly, 3 × 10 3 HARA‐B4 cells (containing GFP from the FG12 vector) were overlaid directly onto confluent MG‐63 cells in a dish and incubated for 30 minutes at 5% CO 2 and 37°C.…”
Section: Methodssupporting
confidence: 74%
“…Osteoblast differentiation was assessed by measuring osteoblast differentiation markers by real‐time PCR, as described previously . The cell adhesion assay was undertaken as described previously . Briefly, 3 × 10 3 HARA‐B4 cells (containing GFP from the FG12 vector) were overlaid directly onto confluent MG‐63 cells in a dish and incubated for 30 minutes at 5% CO 2 and 37°C.…”
Section: Methodssupporting
confidence: 74%
“…13), confirming the key role of endothelial Tie2 during embryonic development. Tie2 is, however, not exclusively expressed by EC1314151617181920. Based on the results of a systematic expression profiling screen of cultured pericytes isolated from different organs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the extensive data on the role of the angiopoietin pathway in angiogenesis, several studies have demonstrated increased expression of Tie2 in cancer cells and in cancer-associated stromal cells. This, coupled with the expression of Ang1 and/or Ang2 by cancer cells and studies of cell lines and in vivo tumor models, suggests that Tie2 activation may contribute to cancer cell growth via additional autocrine mechanisms that promote a stem cell-like phenotype with enhanced adhesion, invasion, and metastatic potential (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%